2015
DOI: 10.1002/ccd.26080
|View full text |Cite
|
Sign up to set email alerts
|

Patent foramen ovale closure following cryptogenic stroke or transient ischaemic attack: Long‐term follow‐up of 301 cases

Abstract: Patent foramen ovale has been identified as a conduit for paradoxical embolism resulting in cryptogenic stroke or transient ischemic attack (TIA). We aimed to establish rates of death, recurrent stroke or TIA among patients undergoing PFO closure for stroke or TIA at our unit. A retrospective analysis of all PFO closure patients was performed between May 2004 and January 2013. Follow up was performed by mortality tracing using the Medical Research Information Service of the Office of National Statistics. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…This has allowed the demonstration of a significant benefit for patients treated with PFO closure with regard to reduction in risk of stroke. Our results are consistent with the findings of the two most recent trials and with the results of recent observational studies that reported that PFO closure was associated with a lower risk of stroke.…”
Section: Discussionsupporting
confidence: 93%
“…This has allowed the demonstration of a significant benefit for patients treated with PFO closure with regard to reduction in risk of stroke. Our results are consistent with the findings of the two most recent trials and with the results of recent observational studies that reported that PFO closure was associated with a lower risk of stroke.…”
Section: Discussionsupporting
confidence: 93%
“…The procedure has acceptably low risks both in the short term, with 2.1% rate of procedural complications all resolved in a few days, and in the long term, with 7.5% rate of events after more than 3 years of medium follow‐up. In particular, recurrent cerebral ischemia is 1.9%, which is consistent with the available literature, reporting occurrence of embolic events ranging from 2.1% during a mean follow‐up of 2.6 years, to 1.6% with a mean follow‐up duration of 40 ± 26 months, to a 0.28% annual/patient risk beyond 5 years’ follow‐up; those data consolidate the role of PFO closure as a secondary prevention after PFO‐related stroke. Atherosclerotic vascular disease progression or silent atrial fibrillation may have played a role in the ischemic recurrences in both groups.…”
Section: Discussionsupporting
confidence: 87%
“…In a study by Mirzaali et al, 301 patients underwent percutaneous PFO closure with 1 of 8 devices, with successful implantation in 99% of cases. Follow‐up duration was 40.2 ± 26.2 months, recurrent stroke (MRI‐ or CT‐confirmed) was observed in 5 patients (0.5%; 0.55 per 100 person‐years) and TIA in 9 (1.1%; 0.98 per 100 person‐years) . In a study by Bardeleben et al, concerning a cumulative follow‐up period of 1265 patient‐years, the recurrence/re‐event rate of cerebral and peripheral thromboembolic events was 0.7% per patient‐year.…”
Section: Discussionmentioning
confidence: 97%